Crime e loucura na biopolítica contemporânea : ética, testemunho e psicanálise - Moscon, Raquel Fabris (2016)
In light of Michel Foucault, we approach the relevant aspects that entwine the fields of psychiatry and law, through the notion of danger - a fundamental term in understanding the policy directed to the psychotic in conflict with the law. To forge a link of intrinsic hazard to mental illness, we show how discourses that govern interventions in this area are grounded in moral conceptions, to ensure social defense against abnormal labeled. We have observed how active mechanisms in the biopolitics of control of those known as abnormal are aimed at the elimination of so-called "dangerous" by subtracting the rights of those viewed as threats to order, and to the political purpose of generating a social set without fail. Simultaneously with the spread of this ideal, they are triggered elimination processes of individuals, through segregation institutions, in which to let one die is legitimized as a strategy in the service of biopolitics. Based on Giorgio Agamben's views, we note that the ideology in vogue in biopolitics updates a discursive totalitarian logic sometimes identified in our contemporary societies in many forms of fixation. Although it has its apex in the exclusion environments, such discourse expands its borders beyond more constrained environments, spreading in the society where the population itself becomes an accomplice in segregation procedures. The ideal of completeness widespread in systems governed by scientism and by capitalism causes impacts on the subjective plane, contaminating the mentality of the people today; similarly, it boosts collective responses, aggravating cases of institutional violence. As for subjectivity, this ideal of completeness produces a permanent state of apathy and identifaction with the objects of satisfaction, resulting in mortification regarding life; however, in relation to social processes, it naturalises exclusion as a legitimate procedure for the survival of the population. The HCTPS, the psychotic shelter institutions in security measure, demonstrate the operability of this mortifying power which falls not only on the inmates internal, but also on the subjectivity of the institution's employees. The narrative of our experience helps to highlight the de-subjectifying consequences found in a controlled environment, where human objectification is actually present.Because of the effects experienced when in contact with this power, we find reasons to evoke the concept of testimony, in a dual mode of inflection found in the term: (a) as a resistance tool and memory duty and (b) according to a clinical perspective, by transforming the traumatic impotence into a narrative of power and transmission. At the end, it is a bet on psychoanalysis as a possible ethical direction. From the teaching of Jacques Lacan in relation to psychosis, it is suggested that the testimony of the person can be an operator in the treatment, opposing the traumatic repetition. The psychoanalytic clinic, when it takes into account the subject’s uniqueness and their unconscious dimension implicated in the crime, favors the development of the cause of suffering from passage to the act, leading to subjective responsibility. The testimony, therefore, appears as a clinical aspect and ethical reorientation of sanitary practice, in which it predominate forms of punishment tha has no meaning and it no use for psychic repair of the subject.